Sacral Space of Ethnic Buryatia: The Cult of Healing Springs - Marina M. Sodnompilova (Oriental Studies)
Introduction. The sacral map of ethnic spatial development is a complicated mosaic of multifunctional zones that includes places of residence, territories for economic activity, and sacral areas proper. Ethnic Buryatia’s sacral map comprises a variety of spatial elements, such as border markers of settlements, places for economic pursuits, burial grounds, and those of hierophanies. ‘Healing’ localities, including healing springs, are somewhat distinguished in this sacral space. Goals. The study attempts a review of images of healing springs, their functions and significance for society — through the prism of spatial, social ‘narratives’ of culture. Materials and methods. The Buryat development space is a compound information environment comprising elements that remain relevant to date. Healing springs are considered from the perspective of the information theory of culture, which makes it possible to identify a few layers of somewhat contradictory messages articulated by representatives of different generations. Results. The paper traces certain chains of changes in statuses of such springs: from ‘water of immortality’ once granted by deities — to symbols of holiness of Buddhist hierarchs whose efforts gave birth to a number of such arshans. Special attention is given to images of supernatural patrons of springs, their healing properties and prescribed practices, beautification endeavors across adjacent territories. Conclusions. The insight into the arshan cult and water-related practices reveals some most socially relevant details inherent thereto. Information layers characterizing the image of a spring reflect certain changes in perceptions of its significance — from clan-level status to public one. Furthermore, Buddhism has yielded significant transformations both in ritual arrangements, patterns of healing practices, and design of such treatment places.